Literature survey of biodegradable polymers. - Koh, Qiu Ling. (2009)
The applications of biodegradable polymers have been mostly focused on three main areas. They are the biomedical, packaging and agricultural applications. Due to their higher unit value and specialization, biomedical applications have developed at a much faster rate than the other two in the past few decades. These useful biomedical applications include controlled drug delivery systems, tissue engineered scaffolds and other medical and therapeutic devices. Biodegradable polymers have been emerging as preferred candidates over many other materials such as ceramics and metals for many biomaterials mainly due to their versatility. In general, there have been so much focus and significant advances in the development of biodegradable polymers that these polymers have established an important role in the biomedical application. This report will present a clear and detailed overview on the current status of the common biodegradable polymers used for biomedical applications and the future prospects they are likely to bring. Some of these extensively investigated and used polymers include polyglycolide, polylactide, poly(lactide-co-glycolide), polycaprolactone, polydioxanone and polyanhydrides. The commercially available products based on these polymers will be presented as well.